The protector [large type] - Brunstetter, Wanda E. (Brunstetter Wanda E. Mifflin County mystery, 2024)
"Rosa Petersheim has disappeared from the Big Valley without a trace. Norman always considered himself his sister's protector and can't believe she would have left home of her own accord ----so he must have failed her. He throws all he has into helping the authorities search for Rosa, while trying to support his parents and siblings who are struggling both mentally and physically. Salina Swarey loves Norman and hopes they are headed towards marriage, but his obsession with Rosa's whereabouts is driving them apart. Can Norman find a place of peace and contentment if he never learns where Rosa Is?" -- back cover